Comparative Biochemical Characterization of Hydrocarbon-Degrading Bacteria on Petroleum-Contaminated Soils from Baranyonwa-Dere in Gokana and Non-Contaminated Soils from Rukpokwu in Obio/Akpor L.G.A, Rivers State, Nigeria - Killian, Emmanuel; Ndekhedehe, Etim; Ehiaghe, Joy (Covenant Journal of Physical and Life Sciences, 2025)
This study presents a comparative biochemical evaluation of hydrocarbon-degrading bacteria (HDB) isolated from petroleum contaminated soil in Baranyonwa-Dere (B-Dere), Gokana LGA, and non-contaminated soil from Rukpokwu, Obio/Akpor LGA, Rivers State, Nigeria. Using culture-dependent methods and standard biochemical assays, five bacterial genera were identified across both sites: Pseudomonas sp., Salmonella sp., Citrobacter sp., Bacillus megaterium, and Bacillus subtilis. However, isolates from the contaminated site demonstrated significantly higher enzymatic activities, including catalase, urease, succinate dehydrogenase, peroxidase, and protease. Among the isolates, Bacillus subtilis from the polluted soil exhibited the highest catalase (730.73 ± 79.92 µmol/mL/min) and urease (0.25 ± 0.01 mg/g/min) activities, while Pseudomonas sp. recorded peak succinate dehydrogenase activity (5.67 ± 0.01 µmol/mL/min). Bacillus megaterium excelled in peroxidase (76.04 ± 0.01 µmol/mL/min) and protease (91.08 ± 0.68 units/mg) activities. In contrast, isolates from the non-contaminated site exhibited comparatively lower enzymatic expression, indicating reduced metabolic demand and hydrocarbon stress. Catalase activity was significantly dominant (p < 0.001) in the polluted environment, suggesting its pivotal role in microbial oxidative stress management and survival in petroleum-rich soils. These findings confirm that oil contamination selectively enhances the diversity and enzymatic adaptation of indigenous bacteria, equipping them for effective hydrocarbon degradation. The elevated metabolic activities in contaminated soils underscore the potential of these native strains as viable bioremediation agents. Harnessing their enzymatic profiles offers a sustainable and eco-friendly strategy for restoring oil-polluted environments in the Niger Delta and similar regions globally.